Carbody sway behaviour of railway vehicles due to track irregularity from rail alternate side wear - Lai Wei; Jing Zeng; Ren Luo; Feng Gan; Jijun Gong; Jun Jiang (Railway Engineering Science)
Abstract Track irregularity from rail alternate side wear is manifested as uneven rail wear waveforms alternating in the left and right rails with equal intervals, which will cause carbody sway behaviour of railway vehicles and greatly influences the passenger comfort. In this work, the carbody sway behaviour and mechanism due to track irregularity from rail alternate side wear and possible solutions to this issue were studied by the field testing and numerical calculation approaches. First, the carbody sway of an urban rail transit train is introduced with full-scale field tests, through which the rail alternate side wear is characterized and the formatted track irregularity are presented. Then, multibody vehicle dynamic models are developed to reproduce the carbody sway behaviour induced by the track irregularity from the rail alternate side wear. The creep forces acting on the wheel and rail are preliminarily discussed to study the influence of the carbody sway on the wear of the wheel flange and the rail corner. Finally, some potential solutions, e.g. improving the damping ratio of carbody rigid mode and rail grinding, are proposed to relieve this issue. It is concluded that an increased damping ratio of the carbody mode can alleviate the carbody sway and wheel–rail interactions, while properly maintaining track conditions can improve the vehicle performance.